Utilization of Learning Management Systems (LMS) Salam Al Azhar as the Learning Process in Al Azhar 35 Islamic International Primary School - Nissa Auwliya Luth Dendy; Lu Wang (Ridwan Institute, 2023)
This paper explores the use of Learning Management Systems (LMS) in a primary school setting, focusing on Al Azhar 35 Islamic Primary School. LMS offers numerous advantages over traditional learning systems, and its application in primary schools is relatively rare in Indonesia. The study employs the Process Mining Project Methodology (PM2) to analyze LMS data, assess its readiness, and examine its suitability for process mining. The study identifies structured data with relevant Case ID, Activity, and Timestamp fields, indicating the data's suitability for process mining. The frequently observed LMS activities include Dashboard, Course Overview, and My Course. These activities are analyzed to assess the LMS's practicality, efficiency, and advantages. The findings reveal that LMS is beneficial for both teachers and students. The study concludes that PM2 methodology is a suitable approach for process mining in education, and the data from Al Azhar 35's LMS is ready for analysis. Future research opportunities include analyzing the learning processes in more diverse case studies, improving data quality, and exploring learning patterns in various classes, semesters, and courses.